Kepuasan Sebagai Mediasi Pengaruh Bauran Pemasaran Terhadap Loyalitas Konsumen Teh Botol Sosro Di Wilayah Surabaya - Nova Ely Tiana; Endang Setyawati (BIP's JURNAL BISNIS PERSPEKTIF, 2012)
Theoretically the marketing mix (product, price, promotion, and distribution) affects satisfaction. If consumers are satisfied then become loyal customers. Currently in the beverage packaging face many competitors. If the consumer is not satisfied with a product then it will switch to choose a competing product. Hence the company should make marketing mix strategies for consumers to form positive perceptions and increased loyalty.The purpose of this study was to determine the influence of the marketing mix of satisfaction and customer loyalty. This study also to examine the mediating role of satisfaction as the marketing mix to customer loyalty. The research was conducted on consumer Teh Botol Sosro in South Surabaya area. Determination of the sample using a non-probability sampling, the accidental sampling. Data were collected at random from the 100 respondents and in the analysis using SPSS 13.0 program. The results showed that the products and promotions directly affects customer satisfaction and loyalty. So also with satisfaction directly affects customer loyalty. This shows that the satisfaction acts as a mediating influence of the marketing mix and promotional products for consumer loyalty.